Mahmud Kamil an-Naqah’s Linguistic Thought: Implications for Arabic Language Teaching for Non-Native Speakers - Ahmad Munawir Hamid; Haniah Haniah; Amrah Kasim (Fakultas Tarbiyah dan Keguruan, 2026)
Purpose – This study analyzes the fundamental concepts of Mahmud Kamil an-Naqah’s linguistic thought and examines their implications for the development of curriculum, methods, and evaluation in Arabic language teaching for non-native speakers. Design/methods/approach – The research used a qualitative descriptive-analytical design grounded in biographical study and library research, the study examined an-Naqah’s primary works and relevant secondary literature through content analysis. Findings – The findings show that his framework is rooted in Arabic linguistics, applied linguistics, and language learning theory, with communicative language use positioned at the center of instruction. The study also finds that the four language skills are treated as integrated competencies, while grammar functions as a supporting element, and that needs analysis, learner characteristics, communicative performance, and psychological variables are central to effective Arabic instruction. The study is limited by its reliance on conceptual and literature-based analysis, without direct classroom testing of an-Naqah’s model. Further research is recommended to examine its implementation in diverse educational settings and to evaluate its effectiveness through empirical and mixed-method designs. Research Implications – These findings indicate that an-Naqah offers a practical paradigm for shifting Arabic pedagogy from rigid structural-grammatical instruction toward a more functional, contextual, and applied model.